Quality Analysis of Dapodik Application Systems in the Department of Education in the City of Palembang Using Delone and Mclean Methods - Nadela Annggela; Ria Andryani (Budapest International Research and Critics University, 2022)
The Dapodik application is a web-based data collection application that is one of the main sources in the formulation of government policies. In the Dapodik application, there are several data that are managed including school data, infrastructure, students, teachers and education staff. The data or information generated, is influenced by the quality of the Dapodik application itself. Therefore, this study aims to conduct a quality analysis of the Dapodik application system using the Delone and Mclean methods. This research is a quantitative descriptive study. The research used the Delone and Mclean Method which contained 6 variables, namely: 1. System Quality (KS), 2. Quality of Information (KI), 3. Quality of Service (TOS), 4. Usage (P), 5. User Satisfaction (KP), 6. Net Benefit (MB).